1986
DOI: 10.1128/jb.168.3.1147-1154.1986
|View full text |Cite
|
Sign up to set email alerts
|

Comparative action of glyphosate as a trigger of energy drain in eubacteria

Abstract: Escherichia coli, Bacillus subtilis, and Pseudomonas aeruginosa, each possessing a 5-enolpyruvylshikimate 3-phosphate synthase that is sensitive to inhibition by glyphosate [N-(phosphonomethyl)glycitie], provide a good cross-section of organisms exemplifying the biochemical diversity of the aromatic pathway targeted by this potent antimicrobial compound. The pattern of growth inhibition, the alteration in levels of aromatic-pathway enzynies, and the accumulation of early-pathway metabolites after the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 36 publications
4
54
1
4
Order By: Relevance
“…Significant derepression of AroA II was not observed when a culture in the mid-exponential stage of growth in rich medium was centrifuged and resuspended in minimal medium for 2 h prior to extract preparation. As another approach, a culture in minimal medium was exposed to 10 mM glyphosate to cause starvation for aromatic amino acids (9). Although growth inhibition was observed, derepression of AroA II did not occur.…”
Section: Resultsmentioning
confidence: 99%
“…Significant derepression of AroA II was not observed when a culture in the mid-exponential stage of growth in rich medium was centrifuged and resuspended in minimal medium for 2 h prior to extract preparation. As another approach, a culture in minimal medium was exposed to 10 mM glyphosate to cause starvation for aromatic amino acids (9). Although growth inhibition was observed, derepression of AroA II did not occur.…”
Section: Resultsmentioning
confidence: 99%
“…Both Synechocystis 6803 and A. variabilis showed tolerance towards the free acid of glyphosate, with little or no inhibition of growth even at 20 mM, compared with total inhibition of growth by 5 mM free acid found for other bacteria (Shulz et al., 1984;Fischer et al, 1986;Pipke et al, 1987), The two species of cyanobacteria studied showed some tolerance to the isopropylamine salt of glyphosate although this compound was more toxic than the free acid. Roundup was the most toxic formulation though it was far less toxic towards Synechocystis 6803 than towards A. variabilis.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of plant tissue cultures is inhibited by < 1 mM glyphosate (Rubin, Gaines and Jensen, 1984;Smarter a/., 1985;Steinrucken et al,, 1986), while bacteria are generally resistant to between 2 mM and 5 mM glypbosate (Schulz, Sost & Amrhein, 1984;Fischer et al 1986;Pipke et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…2.5.1.19, CP4 EPSPS), com peptídio sinal, da via do chiquimato, resistente ao glifosato, mantendo ativa a via biossintética de aminoácidos aromáticos nas plantas. Essa via de biossíntese é inibida em genótipos de soja não modificada (NM), sem a isoforma CP4 EPSPS (BUSSE et al, 2001), tendo em vista que o herbicida glifosato [(N-(fosfonometil) glicina, Roundup (Monsanto, St. Loius, MO)], inibe a síntese de aminoácidos aromáticos (fenilalanina, triptofano e tirosina) em plantas (FISHER et al, 1986). O mecanismo de ação do glifosato compreende a inibição da EPSPS, que catalisa a condensação do ácido chiquímico e fosfofenolpiruvato, dando origem à bioconversão de aminoácidos aromáticos.…”
unclassified
“…A inibição da via de shiquimato pelo glifosato resulta na acumulação do ácido chiquímico e/ou ácidos hidroxibenzoicos, bem como de ácidos protocatequímicos e/ou ácidos gálicos em espécies de plantas sensíveis (DUKE, 1988) e em Bradyrizobium japonicum (ZABLOTOVICZ & REDDY, 2004). Efeitos tóxicos do glifosato podem ser atribuídos à inibição da síntese de aminoácidos aromáticos, à exaustão energética resultante do consumo de adenosina trifosfato (ATP) e fosfofenolpiruvato na síntese do chiquimato, ao 3-deoxi-D-arabino-heptulose-7-fosfato, aos ácidos hidroxibenzóicos e gálico e à toxidade resultante do acúmulo de moléculas intermediárias na via do shiquimato (FISHER et al, 1986). Desse modo, é possível que haja alterações no metabolismo secundário, incluindo a síntese de compostos fenólicos, que inclui esses metabólitos (REDDY et al, 2000).…”
unclassified